PRAKTIK JUAL BELI BERBASIS INFORMATIKA DAN TRANSAKSI ELEKTRONIK PERSPEKTIF UU NO 19 TAHUN 2016 DAN HUKUM EKONOMI SYARIAH - Billah, Akrim (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2023)
Law No. 19 of 2016 regulates the regulation of legal legality of buying and selling based on information and electronic transactions supported by the law on consumer protection in 1999 and trade law no. 14. Likewise, Sharia Economic Law regulates all forms of activities both fertically and horizontally, the existence of Sharia Economic Law as the main reference becomes the benchmark in both social and digital muamalah. 4.0 is an era where the digital world dominates all